Pantasma: Evidence for a Pleistocene circa 14 km diameter impact crater in Nicaragua. (11th February 2019) - Rochette, P.; Alaç, R.; Beck, P.; Brocard, G.; Cavosie, A. J.; Debaille, V.; Devouard, B.; Jourdan, F.; Mougel, B.; Moustard, F.; Moynier, F.; Nomade, S.; et al.
Abstract: The circa 14 km diameter Pantasma circular structure in Oligocene volcanic rocks in Nicaragua is here studied for the first time to understand its origin. Geomorphology, field mapping, and petrographic and geochemical investigations all are consistent with an impact origin for the Pantasma structure. Observations supporting an impact origin include outward‐dipping volcanic flows, the presence of former melt‐bearing polymict breccia, impact glass (with lechatelierite and low H2 O, <300 ppm), and also a possible ejecta layer containing Paleozoic rocks which originated from hundreds of meters below the surface. Diagnostic evidence for impact is provided by detection in impact glass of the former presence of reidite in granular zircon as well as coesite, and extraterrestrial ε 54 Cr value in polymict breccia. Two 40 Ar/ 39 Ar plateau ages with a combined weighted mean age of 815 ± 11 ka (2 σ; P = 0.17) were obtained on impact glass. This age is consistent with geomorphological data and erosion modeling, which all suggest a rather young crater. Pantasma is only the fourth exposed crater >10 km found in the Americas south of N30 latitude, and provides further evidence that a significant number of impact craters may remain to be discovered in Central and South America.